A stripe rust effector Pst18363 targets and stabilises TaNUDX23 that promotes stripe rust disease. Issue 2 (16th October 2019) - Yang, Qian; Huai, Baoyu; Lu, Yuxi; Cai, Kunyan; Guo, Jia; Zhu, Xiaoguo; Kang, Zhensheng; Guo, Jun
Summary: Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), poses a tremendous threat to the production of wheat worldwide. The molecular mechanisms of Pst effectors that regulate wheat immunity are poorly understood. In this study, we identified an effector Pst18363 from Pst that suppresses plant cell death in Nicotiana benthamiana and in wheat. Knocking down Pst18363 expression by virus‐mediated host‐induced gene silencing significantly decreased the number of rust pustules, indicating that Pst18363 functions as an important pathogenicity factor in Pst . Pst18363 was proven to interact with wheat Nudix hydrolase 23 TaNUDX23. In wheat, silencing of TaNUDX23 by virus‐induced gene silencing increased reactive oxygen species (ROS) accumulation induced by the avirulent Pst race CYR23, whereas overexpression of TaNUDX23 suppressed ROS accumulation induced by flg22 in Arabidopsis. In addition, TaNUDX23 suppressed Pst candidate effector Pst322‐trigged cell death by decreasing ROS accumulation in N. benthamiana . Knocking down of TaNUDX23 expression attenuated Pst infection, indicating that TaNUDX23 is a negative regulator of defence. In N. benthamiana, Pst18363 stabilises TaNUDX23. Overall, our data suggest that Pst18363 stabilises TaNUDX23, which suppresses ROS accumulation to facilitate Pst infection.